2019
DOI: 10.17161/jom.v0i82.7057
|View full text |Cite
|
Sign up to set email alerts
|

Generalist solitary ground-nesting bees dominate diversity survey in intensively managed agricultural land

Abstract: In Western Europe agricultural management was intensified in the period 1950–2010 with negative consequences for ecosystem services, such as pollination, especially in countries with a large proportion of agriculture. Farmland represents 66% of the Danish landscape, but little is known about wild bees despite that 75% of the country’s wild and cultivated plant species depend on insect pollination. Strawberry (Fragaria × ananassa) gains considerable benefits from insect pollination and abundance, species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…We documented an effect of the native status of plants cultivated by nurseries on the functional distributions of wild bees present in nurseries, but no effect of landscape-level factors like nursery size or surrounding natural area. While most species and individuals detected were generalist, below ground-nesting, and solitary -as seems to be common in agricultural areas (Ahrenfeldt et al, 2019) -we also detected floral specialists, above-ground cavity nesters, and eusocial species. Moreover, we detected cleptoparasitic species, which serve as indicators of functionally diverse bee assemblages (Sheffield et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…We documented an effect of the native status of plants cultivated by nurseries on the functional distributions of wild bees present in nurseries, but no effect of landscape-level factors like nursery size or surrounding natural area. While most species and individuals detected were generalist, below ground-nesting, and solitary -as seems to be common in agricultural areas (Ahrenfeldt et al, 2019) -we also detected floral specialists, above-ground cavity nesters, and eusocial species. Moreover, we detected cleptoparasitic species, which serve as indicators of functionally diverse bee assemblages (Sheffield et al, 2013).…”
Section: Discussionmentioning
confidence: 52%
“…Different disturbance regimes result in distinct plant communities that in turn shape wild bee communities (Hawkins et al 2015;Neumüller et al 2018). In this context it has been shown, that intensively managed agricultural landscapes are dominated by generalist ground-nesting bee species (Ahrenfeldt et al 2019). In concordance with this assumption, generalist ground-nesting species such as certain species of bumblebees, halictid bees and andrenid bees substantially contributed to the compositional dissimilarity between the three habitat types.…”
Section: Intensively Managed Grasslandmentioning
confidence: 98%
“…The positive effect of extensive grassland can also be ascribed to the associated reduction of intensive arable farming (Kremen et al 2002), as we have found that the proportion of extensively managed grassland is negatively correlated with those of arable land in the studied surroundings. In this context, an increased cover of tilled agricultural land has been shown to reduce bee richness and abundance by reducing floral resources on a landscape scale (Le Féon et al 2010;Ahrenfeldt et al 2019). Furthermore, pesticide seedcoating and spray drift on arable land can contaminate nearby non-target areas (Pimentel 1995;Brittain et al 2010;Botías et al 2016).…”
Section: Arable Landmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of the bees caught in this study were polylectic, i.e. plant generalists, which tend to dominate agricultural landscapes (Ahrenfeldt et al 2019). This generality may help to explain the similarity in bee communities despite the floral differences.…”
Section: Discussionmentioning
confidence: 99%